The Role of NMDA, GLUR4, NF-κB, and Nrf2 in Glaucoma Pathophysiology: Evidence from Wistar Rat Model - Maharani, Maharani; Kartasasmita, Arief Sjamsulaksan; Rahmi, Fifin Luthfia; Rachmawati, Banundari (Journal of Biomedicine and Translational Research, 2026)
Background: Glaucoma is a neurodegenerative disorder involving retinal ganglion cell loss. Elevated intraocular pressure activates the N-methyl-D-aspartate (NMDA) and Glutamate Receptor 4 (GluR4), inducing oxidative stress via the nuclear factor-kappa B (NF-κB) pathway and triggering antioxidant responses through the nuclear factor erythroid 2-related factor 2 (NRF2) pathway, which contributes to disease progression and informs therapeutic insights.Objective: To explore NMDA, GluR4, NF-κB, and NRF2 roles in glaucoma pathophysiology and identify therapeutic targets using Wistar rat models.Methods: This experimental research was conducted using a post-test-only control group design. Fourteen male Wistar rats were divided into two groups (n = 7). The glaucoma group underwent episcleral veincauterization (EVC) to induce a high intraocular pressure (IOP), whereas the control group remained untreated. Four weeks after EVC, evaluations included the expression of NMDA, GluR4, NF-κB, and NRF2 receptors. Statistical significance was defined as a p-value < 0.05. Statistical analysis was performed using a parametric independent t-test and a Mann-Whitney U test.Results: The mean NMDA expression was significantly higher in the glaucoma group (14.50 ± 4.23) compared to the control group (7.74 ± 3.24, p=0.006). Similarly, the mean GluR4 expression was elevated in the glaucoma group (10.77 ±2.40) compared to the control group (3.03 ± 4.05, p = 0.012). The mean NF-κB expression was 14.96 ± 4.87 in the glaucoma group, significantly higher than 6.72 ± 1.84 in the control group (p = 0.003). Conversely, the mean NRF2  expression was significantly lower in the glaucoma group (3.98 ± 1.10) than in the control group (7.18 ± 1.61, p < 0.001).Conclusion: The study highlights significant changes in all four variables, where NMDA, GluR4, NF-κB expressions were higher, and NRF2 expression was lower